Analysis of New Terms in Digital Marketing Innovation Research Themes: Bibliometric Analysis - Muhammad Rosyihuddin; Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The science of studying digital marketing innovation has developed rapidly in the last decade. So, it is necessary to have an in-depth study to find space by further researchers as a form of novelty. This study analyzes the Google Scholar database (last 5 years) through rigorous data selection stages. research analysis using bibliometrics through Publish or Perish and Vos Viewer to get a visual display. The results of the study show that Network visualization (NV) found several new terms related to digital marketing innovation. The results of the Overlay visualization (OV) analysis show that the research trend for digital marketing innovation keywords is still current and developing. Density Visualization (DV) results show that Still There is room for study more continue. The results of this study are expected can give reference in development research digital marketing.